2022
DOI: 10.3390/jcm11092524
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year Follow-Up of Ankle Syndesmotic Injuries: Prospective Comparison of Knotless Suture-Button Fixation and Syndesmotic Screw Fixation

Abstract: Background: Acute syndesmosis injury (ASI) is an indication for surgical stabilization if instability is confirmed. In recent years, fixation using the knotless suture-button (SB) device has become increasingly established as an alternative to set screw fixation (SF). This study directly compared the clinical long-term results after prospective randomized inclusion. Materials and Methods: Between 2011 and 2012, 62 patients with ASI were enrolled in a prospective, randomized, and monocentric study. Forty-one pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
0
12
0
3
Order By: Relevance
“…Our results also showed that the rate of malreduction in the sagittal plane was more frequent than in the coronary direction in the SYS and SBS [ 29 , 38 ]. The rate of malreduction appears to be lower with the use of SBS than with SYS, which is considered a factor for tendentially better clinical outcomes after SBS [ 5 , 15 , 17 , 27 , 42 44 ]. Based on mathematical considerations, which are supported by the studies mentioned above, FNF might represent a possible approach to explain the trend towards better radiological and clinical outcomes after SBS [ 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results also showed that the rate of malreduction in the sagittal plane was more frequent than in the coronary direction in the SYS and SBS [ 29 , 38 ]. The rate of malreduction appears to be lower with the use of SBS than with SYS, which is considered a factor for tendentially better clinical outcomes after SBS [ 5 , 15 , 17 , 27 , 42 44 ]. Based on mathematical considerations, which are supported by the studies mentioned above, FNF might represent a possible approach to explain the trend towards better radiological and clinical outcomes after SBS [ 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to stabilization using a static syndesmotic screw (SYS), which has been performed for decades, stabilization with a suture button system (SBS) was introduced in the 2000s [ 11 , 12 ]. This has proven to be an effective method for stabilizing isolated as well as fracture associated syndesmosis injuries and has become more established in recent years [ 4 , 5 , 13 – 16 ]. SBS tends to lower the rates of malreduction and results in better early postoperative functional outcomes; however, which method should be preferred has not yet been conclusively clarified [ 5 , 10 , 15 , 17 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, discomfort and joint wear may result from syndesmotic injuries that do not go through proper management. Therefore, it is crucial to restore a congruent articulating ankle with stable syndesmosis in order to avoid post-traumatic osteoarthritis, while in rare cases, syndesmosis injury may even cause serious limb-threatening complications [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In misdiagnosis or inadequate treatment of syndesmotic injury, a persistent pain of the ankle, functional disability and early osteoarthritis are potential complications (4) . Thus, anatomic reconstruction of the ankle mortise, stable fixation of disrupted syndesmosis associated with an ankle fracture are essential for optimal outcome (3,5,6) .…”
Section: Introductionmentioning
confidence: 99%